Multiple effects of sibutramine on ejaculation and on vas deferens and seminal vesicle contractility - Nojimoto, Fernanda D. [UNESP]; Piffer, Renata C. [UNESP]; Kiguti, Luiz Ricardo de A. [UNESP]; Lameu, Claudiana; de Camargo, Antonio C. M.; Pereira, Oduvaldo C. M. [UNESP]; Pupo, Andre S. [UNESP] (Academic Press Inc. Elsevier B.V., 2009)
Sibutramine is an inhibitor of norepinephrine and 5-HT reuptake largely used in the management of obesity. Although a fairly safe drug, postmarketing adverse effects of sibutramine were reported including abnormal ejaculation in men. This study investigates the effects of sibutramine on ejaculation and vas deferens and seminal vesicle contractility. Adult male rats received sibutramine (5; 20; or 50 mg kg(-1), ip) and after 60 min were exposed to receptive females for determination of ejaculation parameters. The vasa deferentia and seminal vesicles of untreated rats were mounted in isolated organ baths for recording of isometric contractions and HEK293 cells loaded with fluorescent calcium indicator were used to measure intracellular Ca(2+) transients. Sibutramine 5 and 20 mg kg-1 reduced ejaculation latency whereas 50 mg kg(-1) increased ejaculation latency. Sibutramine 3 to 30 mu M greatly increased the sensitivity of the seminal vesicle and vas deferens to norepinephrine, but at concentrations higher than 10 mu M there were striking depressions of maximal contractions induced by norepinephrine, carbachol and CaCl(2). In HEK293 cells, sibutramine 10 to 100 mu M inhibited intracellular Ca(2+) transients induced by carbachol. Depending on the doses, sibutramine either facilitates or inhibits ejaculation. Apart from its actions in the central nervous system, facilitation of ejaculation may result from augmented sensitivity of smooth muscles to norepinephrine while reductions of intracellular Ca(2+) may be involved in the delayed ejaculation observed with high doses of sibutramine. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Abnormal ejaculation; Premature ejaculation; Seminal vesicle; Sibutramine; Vas deferens